The world from beginnings to 4000 BCE - Tattersall, Ian (New Oxford world history., 2008)
To be human is to be curious. And one of the things we are most curious about is how we came to be who we are--how we evolved over millions of years to become creatures capable of inquiring into our own evolution. In this lively and readable introduction, renowned anthropologist Ian Tattersall thoroughly examines both the fossil and archeological records to trace human evolution from the earliest beginnings of our zoological family Hominidae, through the emergence of Homo sapiens, to the Agricultural Revolution. He begins with an accessible overview of evolutionary theory and then explores the.